Event-related potentials differ between true and false memories in the misinformation paradigm. - Volz, Katja; Stark, Rudolf; Vaitl, Dieter; Ambach, Wolfgang (International journal of psychophysiology : official journal of the International Organization of Psychophysiology, 2019)
Several studies investigating psychophysiological correlates of false memories suggest that psychophysiology may provide incremental information to subjectively reported memory. Based on previous findings in a Deese-Roediger-McDermott paradigm, we examined three components of event-related EEG potentials of memory in a misleading information paradigm. 39 participants watched a video that included eight randomized details (e.g., the color of an envelope). After a retention interval of one week, four out of eight details were replaced by misleading details in a narrative text. Afterward, EEG was derived during a recognition test. First, we found that the amplitude at parietal electrodes did not differ between true and false memories. Instead, parietal positivity was more pronounced during yes- compared to no-responses, indicating parietal positivity reflects subjectively reported memory. Second, we found more positive frontal amplitudes associated with false compared to true memories in late time windows. Consequently, our findings indicate that false memories differ from true memories with respect to late frontal activation. In conclusion, we assume that parietal positivity reflects subjectively experienced memory, whereas late frontal activation holds incremental information to the subjectively experienced and reported memory.
Keywords: *Communication; *Repression, Psychology; Adult; EEG; Electroencephalography/methods; Event-Related Potentials, P300/*physiology; False memory; Female; Humans; Male; Memory; Memory/*physiology; Misinformation paradigm; Reaction Time/*physiology; Young Adult

Atmospheric electromagnetism: Individual differences in brain electrical response to simulated sferics - Schienle, Anne; Stark, Rudolf; Kulzer, Rainer; Klöpper, René; Vaitl, Dieter (International Journal of Psychophysiology, 1996)
The living organism is constantly affected by natural electromagnetic influences covering a wide range of frequencies and amplitudes. One of these natural influences is represented by a phenomenon called atmospherics or sferics. Sferics are very weak electromagnetic impulses generated by atmospheric discharges (lightning). With a newly developed simulation system it was possible to reproduce a previously registered sferics signal and present it to 52 subjects while recording the electroencephalogram (EEG). The repeated application of this stimulus for ten minutes evoked a significant decrease in alpha power in parietal and occipital regions compared to the control condition without sferics presentation. Two constitutional factors were revealed as mediators of sferics effectiveness: the general physical condition of the subjects, and their neuroticism. Individuals with many somatic complaints and a high degree of emotional lability did not respond to the sferics stimulation. This absence of a response is interpreted as an adaptational deficit in reaction to variations in atmospheric parameters.
Keywords: Biometeorology; EEG; Neuroticism; Sferics; Somatic complaints; Weather sensitivity

fMRI BOLD correlates of EEG independent components: spatial correspondence with the default mode network. - Prestel, Marcel; Steinfath, Tim Paul; Tremmel, Michael; Stark, Rudolf; Ott, Ulrich (Frontiers in human neuroscience, 2018)
Goal: We aimed to identify electroencephalographic (EEG) signal fluctuations within independent components (ICs) that correlate to spontaneous blood oxygenation level dependent (BOLD) activity in regions of the default mode network (DMN) during eyes-closed resting state. Methods: We analyzed simultaneously acquired EEG and functional magnetic resonance imaging (fMRI) eyes-closed resting state data in a convenience sample of 30 participants. IC analysis (ICA) was used to decompose the EEG time-series and common ICs were identified using data-driven IC clustering across subjects. The IC time courses were filtered into seven frequency bands, convolved with a hemeodynamic response function (HRF) and used to model spontaneous fMRI signal fluctuations across the brain. In parallel, group ICA analysis was used to decompose the fMRI signal into ICs from which the DMN was identified. Frequency and IC cluster associated hemeodynamic correlation maps obtained from the regression analysis were spatially correlated with the DMN. To investigate the reliability of our findings, the analyses were repeated with data collected from the same subjects 1 year later. Results: Our results indicate a relationship between power fluctuations in the delta, theta, beta and gamma frequency range and the DMN in different EEG ICs in our sample as shown by small to moderate spatial correlations at the first measurement (0.234 < |r| < 0.346, p < 0.0001). Furthermore, activity within an EEG component commonly identified as eye movements correlates with BOLD activity within regions of the DMN. In addition, we demonstrate that correlations between EEG ICs and the BOLD signal during rest are in part stable across time. Discussion: We show that ICA source separated EEG signals can be used to investigate electrophysiological correlates of the DMN. The relationship between the eye movement component and the DMN points to a behavioral association between DMN activity and the level of eye movement or the presence of neuronal activity in this component. Previous findings of an association between frontal midline theta activity and the DMN were replicated.
Keywords: EEG; EEG independent component clustering; default mode network; fMRI; independent component analysis